Home-Based Educational Programs for Management of Dyspnea: A Systematic Literature Review - Chorattas, Aristides; Papastavrou, Evridiki; Charalambous, Andreas; Kouta, Christiana (My University, 2020)
Dyspnea or breathlessness is a symptom of a plethora of diseases; despite that its management poses a challenge, it leads to frequent hospitalizations and a poor quality of life. In lung cancer, dyspnea may appear at any time of the disease but mainly during the end-of-life period. This article aims to explore the effectiveness of home-based educational programs for the management of dyspnea. This is a systematic review. The inclusion criteria were studies published between 2000 and 2018, and structured nurse-led home educational programs for the management of dyspnea due to cancer. The search via PUBMED, COCHRANE, EBSCO, and Google Scholar was worldwide for English- and Greek-language articles. The keywords included “education, program, intervention, patient, dyspnea, breathlessness, cancer, home, nurse.” The review was expanded to dyspnea being due to any chronic disease as it gave only one research article for lung cancer. The review identified seven research articles evaluating the effectiveness of various home-based educational programs for dyspnea management due to chronic obstructive pulmonary disease, heart failure, and lung cancer. They showed that a structured home-based educational program is of benefit for the patients by improving their dyspnea levels and their quality of life. There is the need to evaluate the benefits of home-based educational programs for cancer patients with dyspnea at home either as part of a symptom alone support program or as part of the general support given to cancer patients at home.
Keywords: Education; Program; Patient; Dyspnea; Home; Nurse